2018
DOI: 10.1016/j.ejso.2018.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of plasma D-dimer and fibrinogen in digestive cancer: A systematic review and meta-analysis

Abstract: Both of pretreatment plasma D-dimer and fibrinogen were robust predictors of poor survival in digestive cancer patients with different traits. Further studies are warranted to verify their roles on cancer prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(86 citation statements)
references
References 59 publications
4
78
0
3
Order By: Relevance
“…[25] Fibrinogen concentration before treatment is a known prognostic factor not only in primary and metastatic colorectal cancer but also in other gastrointestinal cancers in terms of overall and disease-free survival. [26,27] Additionally, the concentration of brinogen, which is also an acute phase reactant, is increased during the intense in ammatory response. It was also shown that presurgical systemic in ammatory response increases the risk of infectious postoperative complications, which also include AL.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Fibrinogen concentration before treatment is a known prognostic factor not only in primary and metastatic colorectal cancer but also in other gastrointestinal cancers in terms of overall and disease-free survival. [26,27] Additionally, the concentration of brinogen, which is also an acute phase reactant, is increased during the intense in ammatory response. It was also shown that presurgical systemic in ammatory response increases the risk of infectious postoperative complications, which also include AL.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally regarded as a key factor of coagulation and brinolytic activation. Recently, A lot of research shows that an elevated pre-treatment plasma Fib level is closely associated with poor prognosis in patients with various malignant tumours [18][19][20][21], including breast cancer [12][13][14]. In a large retrospective study of 2073 consecutive breast cancer patients, Wen et al [12] reported that an elevated preoperative plasma Fib level was an independent prognostic factor for overall survival in breast cancer patients who underwent surgical treatment (p=0.001).…”
Section: Discussionmentioning
confidence: 99%
“…We found that preoperative D-dimer and albumin levels in OCCC patients were signi cantly correlated with platinum resistance and were independent predictors of PFS and OS. Patients with cancer often exhibit a state of hypercoagulation and exaggerated brinolysis [22] . D-dimer, as an end product of brinogen, is a signal of the activated coagulation system in numerous cancer types especially in the advanced stage [23,24] .…”
Section: Discussionmentioning
confidence: 99%